CCAFS-validated animal nutrition model for methane emissions in Colombia: a tool to develop low-emission livestock options and strategy - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Stage 4: The Government of Colombia used the adapted RUMINANT model to develop low-emission feed options for livestock in Colombia for their Nationally Appropriate Mitigation Action. The national livestock producer organization also used the model results to inform their national strategy.